КОНЦЕПЦІЯ НАЦІОНАЛЬНОГО В МУЗИЦІ І. ЛЯШЕНКА В УМОВАХ РОЗВИТКУ СУЧАСНОГО ВИКОНАВСЬКОГО МУЗИКОЗНАВСТВА (Педагогіка вищої та середньої школи, 2007)
Clause is devoted to a question of musical sociology as she was generated in works I. Lashenko, which central moment actually has become a problematics of performance musicology, contents, deducing on riches, of performance vision of products. In clause the examples of performance disclosing of national, social idea of music in opera compositions of the outstanding authors are given.